PENGEMBANGAN MODEL MANAJEMEN KURIKULUM 2013 - Utami, Wikan Budi; Amir, Yayat Hidayat; Ponoharjo, Ponoharjo; Aulia, Fikri (Pascasarjana IAIN Kudus, 2019)
The aim of this study is to find a 2013 curriculum management model and provide recommendations to policy makers in developing the 2013 curriculum in the city of Tegal. The implementation of the 2013 curriculum in the city of Tegal is still on a limited scale and there are still many schools that are constrained by the implementation of the 2013 curriculum. This research was carried out at Al-Irsyad High School in the city of Tegal. This type of research is research and development. The results of this study indicate that the 2013 curriculum management model at Al-Irsyad High School in Tegal city was developed through the following steps: curriculum process, planning, curriculum organizing, staffing and curriculum control. The development procedure, is started by conducting a feasibility study and needs and then ends with the implementation of improvements and adjustments after being tested